The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1809-4422asoc300r1v2032017
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Environmental Attitudes and Behaviors: An Exploratory Study With a Sample of Brazilian University Students

Abstract: Models based on a multidimensional structure of environmental attitudes are more appropriate than one-dimensional or dichotomic approaches when assessing the complex relationships people have with the natural environment. This work explores a model of environmental concern composed of four attitudinal dimensions (apathy, anthropocentrism, connectivity and emotional affinity), analyzing their relationships with pro-environmental behaviors. The sample consisted of 250 students from a university that represents t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 32 publications
1
8
0
7
Order By: Relevance
“…In contrast, a study carried out by Amérigo et al (2017) on pro-environmental behavior and attitudes in university students validated a scale to evaluate the explanatory power of four attitudinal dimensions –apathy, anthropocentrism, connectivity and emotional affinity – on three behaviors as follows: energy efficiency and resource management, waste management and organic food consumption. The study was carried out with university students, but the scale neither did not consider the mastery of knowledge nor did it include questions that allowed the exploration of the factors of participants' environment; it also refers to very specific behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a study carried out by Amérigo et al (2017) on pro-environmental behavior and attitudes in university students validated a scale to evaluate the explanatory power of four attitudinal dimensions –apathy, anthropocentrism, connectivity and emotional affinity – on three behaviors as follows: energy efficiency and resource management, waste management and organic food consumption. The study was carried out with university students, but the scale neither did not consider the mastery of knowledge nor did it include questions that allowed the exploration of the factors of participants' environment; it also refers to very specific behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…La investigación tuvo como objetivo principal determinar la relación entre las estrategias de marketing ecológico y el comportamiento proambiental en los estudiantes de un instituto superior tecnológico privado de Lima (Perú) durante el período de tiempo comprendido entre el 01 de agosto hasta el 01 de setiembre del 2019 (hipótesis general) y de las cuatro hipótesis específicas planteadas. Por tal motivo, para la recolección de datos se trabajó con las escalas desarrolladas por Izagirre-Olaizola et al (2013) y Amérigo et al (2017). Posteriormente, el análisis de datos permitió establecer el nivel de asociación entre las variables de estudio.…”
Section: Discussionunclassified
“…It is apparent that psychological variables such as value, beliefs, norm, and attitude are the major antecedents of such behavior (Chua et al 2016(Chua et al , 2019. Moreover, environmental knowledge and information (Chan et al 2017;Díaz-Siefer et al 2015; de Frutos and Egea 2011; Yeoh and Paladino 2013), attitude (Singh and Gupta 2013;Sun et al 2014), awe (Yang et al 2018), personality traits (Puente-Diaz and Arroyo 2015), inclusion of nature in the self-gradient (Amérigo et al 2017), recalled pride and guilt (Rowe et al 2019), and perceived uncertainty (Fernando et al 2018) are also found to be significant predictors of sustainable consumption behavior. Behavioral traits like prosocial behavior (Neaman et al 2018), frugality and restriction and consumption (Muiños et al 2015;Yeniaras and Akarsu 2017), and materialism (Evers et al 2018;Goldsmith et al 2014) are also investigated as the antecedents in the sustainable marketing literature.…”
Section: Dominance Of Psychological Variables In Shaping Sustainable mentioning
confidence: 99%
“…For sustainable marketing studies, many theories have been used in order to understand the relationships between the antecedents and the consequences. In this regard, mostly the authors considered theory of planned behavior (TPB) and value-beliefnorm (VBN) theory and attempted to understand consumers' green value, belief, norm, attitude, intention, and green purchase behavior (Amérigo et al 2017;Chua et al 2019;Dermody et al 2015;Evers et al 2018;Gatersleben et al 2019;Prendergast and Thompson 1998;Rowe et al 2019;Saleki et al 2019;Singh and Gupta 2013;Yang et al 2018;Yeoh and Paladino 2013). In addition, Connelly et al (2011) reviewed nine theories which are transaction cost economics, agency theory, institutional theory, population ecology, resource dependence theory, the resource-based view of the firm, upper echeleons theory, social network theory, and signaling theory in understanding the sustainability aspect.…”
Section: Theory Usedmentioning
confidence: 99%